PENGARUH KOMITMEN ORGANISASI DAN KETIDAKPASTIAN LINGKUNGAN TERHADAP HUBUNGAN ANTARA PARTISIPASI ANGGARAN DENGAN SENJANGAN ANGGARAN PADA PERGURUAN TINGGI SWASTA DI BANJARMASIN - Wahyu Sapto Rini; Gemi Ruwanti; Tjia Fan Nie (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2016)
Abstract, This research aims to examine empirically the independent variables which consists of budget participation, organizational commitment, and environmental affecting the dependent variable of budgetary slack at private colleges in Banjarmasin. Analyses was conducted on 38 respondents to answer the research instruments delivered to lectures who have dual role: the role as lecturer and role as a structural officer at private colleges in Banjarmasin. Hypothesis testing research conducted by multiple linear regression analysis. The results showed that budgetary participation does not affectbudgetary slack, interaction between budgetary participation to goal organizational commitment has positive effect on budgetary slack, and interaction between budgetary participation to environmental does not affect budgetary slack.